2013
DOI: 10.3928/1081597x-20130117-10
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Fixation of a One-Piece Toric Intraocular Lens

Abstract: Purpose To describe a novel technique for toric intraocular lens (IOL) repositioning and fixation in the absence of adequate capsular support Methods Case report and literature review Results Two cases are presented with scleral fixation of a one-piece toric IOL (SN6AT series, Alcon Inc.) In both cases, toric IOLs initially placed within the capsular bag became decentered due to poor capsular support and/or posterior capsule rupture. To avoid the potential complications of lens explantation and maintain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
(12 reference statements)
0
12
2
Order By: Relevance
“…In contrast to earlier reports on scleral fixation of a modern one-piece IOL (Emanuel et al 2013;Rho et al 2015;Leung et al 2016), we found a high incidence of new UGHS in patients with scleral fixated one-piece IOL (24.2%). In the multivariate Cox regression analysis, scleral fixation of a one-piece IOL was a strong independent risk factor for developing UGHS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to earlier reports on scleral fixation of a modern one-piece IOL (Emanuel et al 2013;Rho et al 2015;Leung et al 2016), we found a high incidence of new UGHS in patients with scleral fixated one-piece IOL (24.2%). In the multivariate Cox regression analysis, scleral fixation of a one-piece IOL was a strong independent risk factor for developing UGHS.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to earlier reports on scleral fixation of a modern one‐piece IOL (Emanuel et al. ; Rho et al. ; Leung et al.…”
Section: Discussioncontrasting
confidence: 62%
“…20 8 report in-the-bag suture fixation of a toric IOL with open-loop haptics in settings of a dislocated IOL due to compromised zonular support. Our technique is novel in that this was not an aphakic eye nor was the IOL sutured because of a dislocated capsular bag.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8 We describe a through-the-bag transscleral suture fixation technique to manage recurrent rotation of a hydrophilic acrylic toric IOL with a double-loop haptic design.…”
Section: Online Videomentioning
confidence: 99%
“… 1 , 2 , 3 A large corneal incision changes the corneal shape significantly, and the two-point fixation raises the risk of IOL tilt. Although there have been several reports of scleral fixation of multifocal or toric IOLs, 4 , 5 , 6 , 7 , 8 , 9 the inherent limitations of conventional scleral fixation techniques have hindered the wide use of premium IOLs in patients without sufficient zonular support.…”
Section: Introductionmentioning
confidence: 99%